2011
DOI: 10.1080/03081060.2011.600092
|View full text |Cite
|
Sign up to set email alerts
|

A behavioral analysis of freight mode choice decisions

Abstract: This paper develops a behavioral analysis of freight mode choice decisions that could provide a basis for an acceptable analytical tool for policy assessment. The paper specifically examines the way that truck and rail compete for commodity movement in the US. Two binary mode choice models are introduced in which some shipment-specific variables (e.g. distance, weight and value) and mode-specific variables (e.g. haul time and cost) are found to be determinants. The specifications of the non-selected choice are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 18 publications
3
42
0
Order By: Relevance
“…The point to be mentioned is that some variables of Table 1 are ineffective in forming the tree. Distance variable which in Samimi et al (2011) study is found to be an important variable in this tree is not a good descriptor and therefore not present in the model. Accuracy of the model for truck mode, rail mode and total accuracy are respectively 99.32, 77.78 and 97.70%.…”
Section: Descriptive Models Using C5 Decision Treementioning
confidence: 99%
See 1 more Smart Citation
“…The point to be mentioned is that some variables of Table 1 are ineffective in forming the tree. Distance variable which in Samimi et al (2011) study is found to be an important variable in this tree is not a good descriptor and therefore not present in the model. Accuracy of the model for truck mode, rail mode and total accuracy are respectively 99.32, 77.78 and 97.70%.…”
Section: Descriptive Models Using C5 Decision Treementioning
confidence: 99%
“…Mode choice can be regarded as one of the most substantial decisions of each firm involved in a supply chain (Samimi et al, 2011). Generally stating, in studying behaviour of firms in field of freight mode choice there are much more complicity than mode choice of commuters.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to Samimi et al (2011), Danielis and Marcucci (2007) and Lammgård (2007) notice that there is a willingness to abandon the existing choice of freight service. It is also noted that the logistics managers showed little awareness of the definite features of multimodal transportation and in some cases believed them to lie far outside the acceptable area.…”
Section: Shipment Attributesmentioning
confidence: 99%
“…Evers et al (1996) finds reliability and availability as the highest ranked decision factors for modal choice. Samimi et al (2011) states that the prevailing factors affecting freight mode choice are (in falling order of importance) reliability, cost, transport time, flexibility and past experience with each mode.…”
Section: Shipment Attributesmentioning
confidence: 99%
See 1 more Smart Citation